STAGING OF DEPOSITS' ECONOMIC ASSESSMENT AND ROUGH SHOWINGS OF EXPENSES IN THE EARLY STAGES OF MINERAL RESOURCES' EXPLORATION (Proceedings of the YSU C: Geological and Geographical Sciences, 2007)
The general order and financing sources of mineral resources' exploration, as well as methods of calculation of capital and operational expenses for the mining factory construction and reserves processing are considered in this article.
Keywords: mineral resources’ exploration; annual productivity of a quarry; mining enterprise